Dynamic supply response analysis of Pakistani rice growers - Faiz Muhammad Shaikh; Madad Ali Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2008)
Alternative specifications of model of supply response of Pakistani rice growers and their economic implications are considered in terms of the existences and nature of production lags, and the choice between expected price and gross returns as the preferred explanatory of producer.s response to changing economic condition. The analysis indicates that there are lags which are due primarily to the difficulties and cost of rapid adjustment rather than to the time required to revise expectations. The statistical results were similar for the alternative specification of gross margins and prices as the economic decision available. However, the price elasticities derived using the gross margins specification were about a third of those using the prices specification. The gross margin specification yielded additional information in the form of yield and input cost elasticities.
Keywords: 330; Supply response analysis; Rice growers; Pakistan